A 3D 8-connected bcu topological metal–organic framework built by trinuclear Cd(II) units: Photocatalysis and LC-MS studies. (1st January 2022) - Hong, Wei-Wei; Lu, Lu; Yue, Mei; Huang, Chunchao; Muddassir, Mohd.; Sakiyama, Hiroshi; Wang, Jun
Graphical abstract: [Cd3 (tp)3 (bmi)2 ] (SUSE-1 ) showed effective photocatalytic performance for the disintegration of dyes. A plausible mechanism for the degradation toward MB was suggested by the trapping method and LC-MS studies. Highlights: A new 3D typical 8-connected bcu -type network was designed and synthesized. SUSE-1 showed efficient photocatalytic activity for dyes. The possible degradation intermediates were identified by LC-MS. Abstract: A new metal–organic framework (MOF), namely [Cd3 (tp)3 (bmi)2 ] (SUSE-1, SUSE = Sichuan University of Science & Engineering) (H2 tp = 1, 4-dicarboxybenzene acid and bmi = 1, 3-bis(2-methylimidazolyl)pentane), has been synthesized. It exhibits a typical 8-connected bcu -type network with [Cd3 (COO)6 (bmi)4 ] nodes. SUSE-1 showed effective photocatalytic performance for the disintegration of the dyes Rhodamine B (Rh B), methyl orange (MO) and methylene blue (MB). In addition, a plausible mechanism for the degradation of MB was suggested from the results of the trapping method and LC-MS studies.